2018
DOI: 10.1007/978-3-319-72041-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxide Nanoparticles Induced Transcriptomic Alterations in HEPG2 Cells

Abstract: Nickel oxide nanoparticles (NiO-NPs) are increasingly used and concerns have been raised on its toxicity. Although a few studies have reported the toxicity of NiO-NPs, a comprehensive understanding of NiO-NPs toxicity in human cells is still lagging. In this study, we integrated transcriptomic approach and genotoxic evidence to depict the mechanism of NiO-NPs toxicity in human hepatocellular carcinoma (HepG2) cells. DNA damage analysis was done using comet assay, which showed 26-fold greater tail moment in Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Previous studies indicated the NiO-NPs caused damage in lung and liver and induce pulmonary inflamations via reactive oxygen species (ROS) (Chang et al, 2017;Li et al, 2018;Marzban et al, 2017;Senoh et al, 2017;Shinohara et al, 2017;Yu et al, 2017;Dumala et al, 2018;Ogami et al, 2009). In vitro researches confirmed with the in vivo studies that the NiO-NPs induced an increase in ROS and caused oxidative damage in the cells (Abudayyak et al 2017a;Åkerlund et al, 2018;Di Bucchianico et al, 2018;Mohamed et al, 2018;Saquib et al, 2018). Previous data confirmed with our results; oxidative stress could be the mechansim underlying the cytoand genotoxicity induced by the NiO-NPs .…”
Section: Tablesupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies indicated the NiO-NPs caused damage in lung and liver and induce pulmonary inflamations via reactive oxygen species (ROS) (Chang et al, 2017;Li et al, 2018;Marzban et al, 2017;Senoh et al, 2017;Shinohara et al, 2017;Yu et al, 2017;Dumala et al, 2018;Ogami et al, 2009). In vitro researches confirmed with the in vivo studies that the NiO-NPs induced an increase in ROS and caused oxidative damage in the cells (Abudayyak et al 2017a;Åkerlund et al, 2018;Di Bucchianico et al, 2018;Mohamed et al, 2018;Saquib et al, 2018). Previous data confirmed with our results; oxidative stress could be the mechansim underlying the cytoand genotoxicity induced by the NiO-NPs .…”
Section: Tablesupporting
confidence: 91%
“…The results indicated that apoptosis could be the main cell death pathway in exposure to NiO-NPs. De Bucciani et al (2018) and Saquib et al (2018) observed increase in the apoptotic cells in dose dependent manner (De Bucciani et al, 2018;Saquib et al, 2018). Similarly, Chang et al (2017b) indicated endoplasmic reticulum stress related apoptosis in rat exposed to NiO-NPs by intratracheal instillation (Chang et al, 2017b).…”
Section: Tablementioning
confidence: 96%
See 1 more Smart Citation
“…cerevisiae (Sousa, Soares, & Soares, 2018). The ability of NiO-NPs to induce apoptosis, DNA damage, oxidative stress and alterations in the transcriptome of human liver cells (HepG2) has been well documented (Saquib et al, 2018). De Carli et al (2018) depicted the genotoxicity and mutagenic potential of NiO-NPs by testing on Chinese hamster normal lung fibroblast cells and Drosophila melanogaster, respectively.…”
mentioning
confidence: 99%
“…Despite its wide application, Nano NiO is also known for its harmful effects and draws increasing attention to health science researchers. Nano NiO causes reactive oxygen species (ROS) generation, oxidative stress, DNA damage, apoptosis, and transcriptome alterations in HepG2 cells . In addition, chronic liver damage promotes hepatic fibrosis in animal models .…”
Section: Introductionmentioning
confidence: 99%